The chemistry of gut microbiome in health and diseases - Agnes Wei Yin Lau; Loh Teng-Hern Tan; Nurul-Syakima Ab Mutalib; Sunny Hei Wong; Vengadesh Letchumanan; Learn-Han Lee (Progress in Microbes and Molecular Biology)
There are trillions of microbes residing in our body, with their collective genomes much more than human genomes. They have been living in a close relationship with us and play a role in various biological functions. The human microbes begin to build up in utero, accumulate, and fluctuate until a set point is achieved around three years of age. The gut microbiome is altered by several factors, which include age, diet, and antibiotic use. After the exposure, the microbe may shift back to retain its balance, but some factors may leave a permanent footprint on the gut flora. This may be significant as our review has shown the relationships between microbes and diseases. When the homeostasis of gut-microbes is disrupted, multiple mechanisms have been shown to contribute to diseases' development. The balance between protective and pathogenic microbes must be kept in check to prevent disease onset. With a better understanding of this relationship, we will investigate the potential methods to modify the gut flora as the background of developing therapeutic options. There are already some therapeutic options such as prebiotics, probiotics, and fecal transplantation, but their clinical use is limited and restricted. Therefore, there is still a need to investigate the characteristic microbiome association with gut-dysbiosis-related diseases, which may help manage the disease and develop diagnostic and monitoring tools. This review aims to discuss our gut microbiome and its association with human health and diseases.